2020
DOI: 10.3390/d12050193
|View full text |Cite
|
Sign up to set email alerts
|

Plant Community Assembly in Invaded Recipient Californian Grasslands and Putative Donor Grasslands in Spain

Abstract: The introduction of exotic species to new regions offers opportunities to test fundamental questions in ecology, such as the context-dependency of community structure and assembly. Annual grasslands provide a model system of a major unidirectional introduction of plant species from Europe to North America. We compared the community structure of grasslands in two Mediterranean regions by surveying plots in Spain and in California with similar environmental and management conditions. All species found in Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…As hypothesized, we found that, in both regions, colonizer species assemblages were functionally more diverse than the other coexisting species. This adds to previous evidence that Spanish grassland communities hold greater species richness than California grasslands (Galán Díaz, de la Riva, Parker, et al, 2021;Leiva et al, 1997), and reflects that colonizer species might also dominate the trait space. Some authors suggest that ancient agricultural landscapes in Europe may have created human-mediated niches promoting high levels of biodiversity (Eriksson, 2013).…”
Section: Diversity and Functional Structure Of Species Assemblages Al...supporting
confidence: 74%
See 3 more Smart Citations
“…As hypothesized, we found that, in both regions, colonizer species assemblages were functionally more diverse than the other coexisting species. This adds to previous evidence that Spanish grassland communities hold greater species richness than California grasslands (Galán Díaz, de la Riva, Parker, et al, 2021;Leiva et al, 1997), and reflects that colonizer species might also dominate the trait space. Some authors suggest that ancient agricultural landscapes in Europe may have created human-mediated niches promoting high levels of biodiversity (Eriksson, 2013).…”
Section: Diversity and Functional Structure Of Species Assemblages Al...supporting
confidence: 74%
“…In Spain, we found 139 species, all of them native to Spain (Valdés et al, 1987). In all, 79 were colonizers; 73 are established in California (Calflora., 2014; Galán Díaz, de la Riva, Parker, et al, 2021) and 6 more are established in other Mediterranean regions but were not introduced to California. These six species are expected to share similar traits and so were also considered colonizers (Arianoutsou et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plenty of literature compares abundance between native and invaded ranges and most of them agree that, when both ranges share a vast number of species and environmental conditions, the abundance of alien species is expected to be similar in both, perchance being an indicator of invasion success (Firn et al 2011;Parker et al 2013;Colautti et al 2014;Pearson et al 2018). Furthermore, some studies have already compared the community composition between Mediterranean grasslands in the native and invaded ranges (for example, Leiva et al 1997;Martín-Forés et al 2014), but there are very few that compare their assembly (de Miguel et al 2016;Galán Diaz et al 2020).…”
Section: Introductionmentioning
confidence: 99%